Eosinophilic Gastroenteritis Associated with Rheumatoid Arthritis - Fatma PAKSOY; Turgay ULAŞ; Esat NAMAL; Emine GÜLTÜRK; Timuçin AYDOĞAN; Fatih BORLU6 (Archives of Rheumatology, 2011)
Objectives: In this article we evaluated the relationship between rheumatoid arthritis and eosinophilic gastroenteritis. Patients and methods: A 71-year-old female patient with a diagnosis of rheumatoid artritis was admitted to our clinic with gastrointestinal symptoms and peripheral eosinophilia. We examined the patient via gastrointestinal endoscopy, ultrasonography, computed tomography, stool analysis, and biochemical analysis. Results: Gastrointestinal endoscopy revealed esophageal dysmotility, pangastritis, and duedonal erythema. Histopathologic examinations revealed subacute and chronic inflammation with dense eosinophilic infiltration. Stool analyses were negative for fat, parasites, and other pathogens. The results for ultrasonograpy and computed tomographies were normal. Conclusion: This brief report showed us the importance of conducting further analysis when a patient with rheumatoid arthritis presents with peripheral eosinophilia and gastrointestinal discomfort. It also represents the possible coexistence of rheumatoid arthritis and eosinophilic gastroenteritis without an apparent etiology.